2014
DOI: 10.3896/ibra.1.53.1.01
|View full text |Cite
|
Sign up to set email alerts
|

A national survey of managed honey bee 2012–2013 annual colony losses in the USA: results from the Bee Informed Partnership

Abstract: SummaryFor the past six years in which overwintering mortality of honey bee colonies has been surveyed in the USA, estimates of colony loss have fluctuated around one-third of the national population. Here we report on the losses for the 2012-2013 seasons. We collected data from 6,482 US beekeepers (6,114 backyard, 233 sideline, and 135 commercial beekeepers) to document overwintering mortality rates of honey bee colonies for the USA. Responding beekeepers reported a total 30.6% (95% CI: 30.16-31.13%) loss of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
192
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(207 citation statements)
references
References 26 publications
10
192
1
4
Order By: Relevance
“…The European honeybee does not express these traits at a level at which they confer tolerance to the parasite ). This became obvious after the mite shifted host from A. cerana to A. mellifera L. (Rath and Drescher 1990;Solignac et al 2005) and became responsible for the mortality of a large number of honeybee colonies in several regions of the world where it has spread (see references in Dietemann et al 2012;van Dooremalen et al 2013;Spleen et al 2013;Steinhauer et al 2014). Apis mellifera colonies cannot survive without chemical treatment against Varroa mites and colonies usually die within one to three years if left untreated (Martin 1998;Rosenkranz et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The European honeybee does not express these traits at a level at which they confer tolerance to the parasite ). This became obvious after the mite shifted host from A. cerana to A. mellifera L. (Rath and Drescher 1990;Solignac et al 2005) and became responsible for the mortality of a large number of honeybee colonies in several regions of the world where it has spread (see references in Dietemann et al 2012;van Dooremalen et al 2013;Spleen et al 2013;Steinhauer et al 2014). Apis mellifera colonies cannot survive without chemical treatment against Varroa mites and colonies usually die within one to three years if left untreated (Martin 1998;Rosenkranz et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Although no reference values exist for the acceptable level of colony losses during winter, various acceptable rates of winter colony mortality were reported in European countries (Charrière and Neumann 2010;Genersch et al 2010) and outside Europe (Head et al 2010;Steinhauer et al 2014). The seasonal mortality rates of each country were compared to the mean seasonal mortality of participating countries.…”
Section: Univariate Analysismentioning
confidence: 99%
“…Many publications that looked into colony losses from any part of the world reported that several biological and environmental factors acting alone or in combination have the potential to cause premature colony mortality (Genersch et al 2010;Potts et al 2010; Spleen et al 2013). In the USA and Canada, alarming losses of honeybee colonies were recently reported (Steinhauer et al 2014). In Europe, the decrease in honeybee colonies was estimated at Corresponding author: M. Chauzat, marie-…”
Section: Introductionmentioning
confidence: 99%
“…Declines in honey bee colony health and high colony losses have been reported by beekeepers over the last decade at rates, ranging from 23 to 41% (Lee et al, 2015b;Spleen et al, 2013;Steinhauer et al, 2014;Seitz et al, 2015;vanEngelsdorp et al, 2010;vanEngelsdorp et al, 2011;vanEngelsdorp et al, 2012). These levels are noticeably higher than the economically sustainable losses of about 15% reported by the US beekeepers (Steinhauer et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…These levels are noticeably higher than the economically sustainable losses of about 15% reported by the US beekeepers (Steinhauer et al, 2014). Many stressors, including pests, pathogens, agricultural intensification, poor nutrition, improper management practices, failing queens, and pesticide exposure have been identified as contributing to continued high losses (Evans et al, 2009;Seitz et al, 2015).…”
Section: Introductionmentioning
confidence: 99%